2012
DOI: 10.1109/jsen.2011.2179532
|View full text |Cite
|
Sign up to set email alerts
|

Various Compositions to Form a Triad of Collocated Dipoles/Loops, for Direction Finding and Polarization Estimation

Abstract: To form a collocated triad of orthogonally oriented dipole(s) and/or loop(s), 20 different compositions are possible. For each such composition: 1) closed-form formulas are produced here to estimate the azimuth-elevation direction-of-arrival and the polarization-parameters from an ambiguous steering vector subject to an unknown complex-value multiplicative coefficient; or 2) reasoning is given why such estimation is inviable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…tripole) has been investigated by Comption Jr. [46,47]. The dipole-triad (array) was used for direction finding in [48][49][50][51][52]. The performance of a dipole-triad array for 1D direction finding and polarization estimation has been evaluated in [48] through the CRBs derivation, and it showed that the quality of the DOA estimate depends strongly on the polarization state.…”
Section: Introductionmentioning
confidence: 99%
“…tripole) has been investigated by Comption Jr. [46,47]. The dipole-triad (array) was used for direction finding in [48][49][50][51][52]. The performance of a dipole-triad array for 1D direction finding and polarization estimation has been evaluated in [48] through the CRBs derivation, and it showed that the quality of the DOA estimate depends strongly on the polarization state.…”
Section: Introductionmentioning
confidence: 99%
“…For the CLD pairs, the dipoles parallel to the z-axis are referred to as the z-axis dipoles and the loops parallel to the x-y plane as the x-y plane loops, respectively measuring the z-axis electric field components and the z-axis magnetic field components. The CLD pairs' steering vector of the kth (1 ≤ k ≤ K) unit-power electromagnetic source signal is the following 2 × 1 vector [4,26]:…”
Section: Problem Formulationmentioning
confidence: 99%
“…It is very difficult to calculate a coarse DOA estimation [33] from the estimated steering vectorb(u k , f k , g k , h k ) of an orthogonally oriented and spatially separated dipole-triad due to the spatial phase factor d(θ, f). Therefore, the conventional disambiguation method [6,32] using the coarse estimation as a reference to disambiguate the cyclically ambiguous estimation cannot be used.…”
Section: Virtual Fine-coarse Estimate Fitting For Disambiguationmentioning
confidence: 99%
“…whereû (h,l) Using the closed-form formulas of the azimuth-elevation DOA estimation from the array manifold of a spatially collocated dipole-triad from [33], the virtual coarse azimuth-elevation DOA estimation can be expressed as (see (21)) where q (h,l)…”
Section: Virtual Fine-coarse Estimate Fitting For Disambiguationmentioning
confidence: 99%
See 1 more Smart Citation